2003
DOI: 10.18553/jmcp.2003.9.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Value and Quality of Health Economic Analyses: Implications of Utilizing the QHES

Abstract: An examination of the QHES validation study and the case study in GERD suggests that there is a rationale and potential utility to use a quality scoring system for cost-effectiveness studies. The QHES may play an important role in discriminating higher-quality cost-effectiveness information to enhance decision making. The QHES can also serve as a guideline for conducting and reporting future cost-effectiveness studies, as an aid in the editorial process, and for stratification in systematic reviews. Complex de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
262
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(272 citation statements)
references
References 68 publications
2
262
0
5
Order By: Relevance
“…[34][35][36][37][38][39][40][41][42][43][44][45][46][47] In addition, two studies performed a multiway sensitivity analysis 37,45 and nine studies a probabilistic sensitivity analysis (PSA). 35,[37][38][39][40][41][42][43]46 Quality assessment A review of Szucs et al 49 evaluated the quality of 11 of the included studies using the British Medical Journal (BMJ)'s checklist by Drummond and Jefferson 50 and the "Quality of Health Economic Studies" evaluation tool by Ofman et al 51 Szucs et al 49 concluded that the quality of these studies varied from 'Moderate' 37,38,4337,38,43 to 'Moderate-Good' 35,36,[39][40][41][42]44 . We assessed the three other included studies using the same criteria as Szucs et al 49 used.…”
Section: Study Selectionmentioning
confidence: 99%
“…[34][35][36][37][38][39][40][41][42][43][44][45][46][47] In addition, two studies performed a multiway sensitivity analysis 37,45 and nine studies a probabilistic sensitivity analysis (PSA). 35,[37][38][39][40][41][42][43]46 Quality assessment A review of Szucs et al 49 evaluated the quality of 11 of the included studies using the British Medical Journal (BMJ)'s checklist by Drummond and Jefferson 50 and the "Quality of Health Economic Studies" evaluation tool by Ofman et al 51 Szucs et al 49 concluded that the quality of these studies varied from 'Moderate' 37,38,4337,38,43 to 'Moderate-Good' 35,36,[39][40][41][42]44 . We assessed the three other included studies using the same criteria as Szucs et al 49 used.…”
Section: Study Selectionmentioning
confidence: 99%
“…In this study, a review of the pharmacoeconomic evaluations for the use of Levodopa in Parkinson's disease was carried out, based on the QHES instrument [22], which qualifies methodological quality and has been used by other authors previously [45][46][47][48][49].Only the articles that met inclusion criteria and were considered of cost-utility were taken, finding that the five articles analyzed obtained an overall average score of 77.2 out of 100. This reflects that these studies are of good quality, and this is probably attributable to the fact that they were recently carried out following the current guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The QHES (Quality of Health Economic Studies) instrument was implemented to evaluate the selected articles [22]. 16 criteria were established in the instrument, which determined the three types of health care economic analysis: minimizing costs, costeffectiveness, cost-utility; as shown in Table 1.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Responses are binary and questions answered ''yes'' receive the full point value, whereas questions answered ''no'' receive zero points. The questionnaire was derived by a panel of eight experts in health economics and the point values were derived using a random-effects general least-squares regression based on a conjoint analysis of survey results from 120 international health economists [41]. Cumulative scores for the Quality of Health Economic Studies instrument range from 0 to 100.…”
Section: Quality Scoringmentioning
confidence: 99%